Industrialization increases the estrogen-recycling capacity of the gut microbiome - Rebecca S. A. Brittain; Richard G. Bribiescas; Grazyna Jasienska (Proceedings of the National Academy of Sciences, 2026)
Estrogens influence many aspects of human physiology and health, including fertility, growth, metabolic function, and susceptibility to disease. Up to 65% of circulating estrogens are excreted into the gut via bile, but only 10-15% are eliminated in feces, indicating substantial estrogen reabsorption [H. Adlercreutz and P. Järvenpää, J. Steroid Biochem. 17 , 639–645 (1982); A. A. Sandberg and W. R. Slaunwhite, J. Clin. Investig. 36 , 1266–1278 (1957)]. This estrogen recycling is enabled by the gut estrobolome, a subset of microbes that deconjugate conjugated estrogens in the gastrointestinal tract, facilitating their reabsorption into systemic circulation [C. S. Plottel and M. J. Blaser, Cell Host Microbe 10 , 324–335 (2011)]. To date, it is not known if populations differ in this microbial function, and little is known about its determinants. Here we analyze estrobolomes using publicly available gut microbiome data from 24 populations spanning four continents and subsistence modes ranging from hunting and gathering to pastoralism, rural farming, and industrialized agriculture. We show that industrialized populations exhibit up to seven times greater estrogen-recycling capacity and nearly twofold higher estrobolome diversity compared with nonindustrial groups. We further find that formula-fed infants display two- to threefold higher recycling capacity and as much as eleven times greater estrobolome diversity than breastfed counterparts, revealing early-life divergence in microbial estrogen metabolism. By contrast, sex, age, and BMI are not associated with estrobolome characteristics. These findings demonstrate the crucial impact of industrialized lifestyles, including formula feeding, on the microbial capacity to influence systemic estrogen levels, with implications for life history, reproductive biology, and estrogen-associated diseases, including cancer.